Contagion of credit risk: Comparative analysis before and after the pandemic of COVID‐19. Issue 4 (23rd May 2022) - Ito, Takayasu
Abstract: The spreads of credit default swaps (CDS) in Germany, Japan, United Kingdom, and United States move together before the COVID‐19 pandemic with few mutual causalities. However, they do not move together after the pandemic and have more mutual causalities. The credit risk of four major countries—Germany, Japan, United Kingdom, and United States are connected due to their relative stability before the pandemic. However, they are not connected in terms of the differences in public spending between the countries during COVID‐19. This makes the CDS market more sensitive to credit risk in each nation, resulting in the independent move of credit risk among the four countries.